Kansas Farm Management Association enterprise analysis: Examining differences among high-, medium-, and low-profit dairy operations - Dhuyvetter, Kevin C.; Kastens, Terry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty-one dairy producers participated in the Kansas Farm Management Association (KFMA) dairy enterprise analysis each year from 2002 to 2004. The dairy farms were sorted based on 3-year average returns over total costs and were categorized as high-, medium-, and low-profit farms. The highestprofit farms earned an average of $795 more per cow ($4.20 per cwt of milk) than the lowprofit farms earned. High-profit farms averaged $521 more milk sales per cow than lowprofit farms did. This difference in profitability was due entirely to greater milk production, inasmuch as milk prices among profit groups did not differ from each other. Highprofit farms produced almost 4,000 lb more milk per cow per year and had slightly lower costs than low-profit farms had. Returns for the mid-profit farms were more than $400 per cow less than returns of the top farms, but were more than $350 per cow greater than those of low-profit farms. The mid-profit farms had production levels similar to those of the high-profit farms, but their costs were significantly greater. Over the 3 years analyzed, it was better to have high production and high costs than to have low production and low costs. But these 3-year averages indicate that dairies can achieve high production levels while keeping costs in check, and these operations are significantly more profitable than other dairies.
Dairy Research, 2005 is known as Dairy Day, 2005
Keywords: Dairy; Cost; Economics; Management; Profitability